The Efficacy of Migration Policies in Addressing Migration Issues: An Analysis on the Situation of Zep Holders - Ndebele, Nomazulu (University of the Witwatersrand, Johannesburg, 2024)
This study comprehensively analyses the efficacy of migration policies in ensuring the welfare of ZEP holders in South Africa by examining the intersection between migration, policies, and life experiences of ZEP holders. Using a qualitative research method to compare the experiences of ZEP and non-ZEP holders, this study explores the challenges and opportunities faced by Zimbabwean migrants with different legal statuses against inconsistent migration regulations and changing socioeconomics. This study reveals the importance of legal migration status in shaping the lives of migrants and the impact of migration policies on ZEP holders. The study further emphasises the consideration of different experiences of ZEP holders, ranging from labour migrants to asylum seekers, where different migrant categories were mixed under one migration regulation program. It is against the grouping of different migrant categories under the ZEP program and calls for inclusive and sustainable policies, emphasising addressing migration problems from their root cause to ensuring migrant welfare in the host country.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Migration Policies; Zimbabwean Exemption Permit (ZEP); Legal Status; Employment Opportunities; Social Integration; Policy Effectiveness; Asylum Seekers; Labor Migrants; Human Rights; SDG-10: Reduced inequalities